Heading Direction Is Significantly Biased by Preceding Whole-Body Roll-Orientation While Lying - Tarnutzer, Alexander Andrea; Duarte da Costa, Vasco; Baumann, Denise; Hemm, Simone (Frontiers in Neurology, 2022)
Background: After prolonged static whole-body roll-tilt a significant bias of internal estimates of direction of gravity has been observed when assessing the subjective visual vertical. Objective: We hypothesized that this post-tilt bias represents a more general phenomenon, broadly affecting spatial orientation and navigation. Specifically, we predicted that after prolonged roll-tilt to either side perceived straight-ahead will be biased as well. Methods: Twenty-five healthy participants were asked to rest in three different lying positions (supine, right-ear-down, left-ear-down) for five minutes (“adaptation period”) prior to walking straight-ahead blindfolded for two minutes. Walking was recorded with inertial measurement unit sensors attached to different body locations and with sensor shoe insoles. Raw data was segmented with a gait-event detection method. Heading direction was determined and linear mixed-effects models were used for statistical analyses. Results: A significant bias in heading into the direction of the previous roll-tilt position was ob-served in the post-adaptation trials. This bias was identified in both measurement systems and de-creased again over the two-minute walking period. Conclusions: The bias observed further confirms the influence of prior knowledge on spatial ori-entation and navigation. Specifically, it underlines the broad impact of a shifting internal estimate of direction of gravity over a range of distinct paradigms, illustrating similar decay time constants. In the broader context, the observed bias in perceived straight-ahead emphasizes that getting up in the morning after a good night’s sleep is a vulnerable period, with an increased risk of falls and fall-related injuries due to not optimally tuned internal estimates of direction of gravity and direction of straight-ahead.